Sorcery, Revenge, and Anti-Revenge: Relational Excess and Individuation in the Gran Chaco. Issue 2 (1st June 2019) - Tola, Florencia
Abstract : This article focuses on sorcery, revenge, and anti-revenge among the Qom people in Argentina. For them, death is the result of sorcery or a shamanic attack. When a relative dies, the family may decide to avenge him through practices performed on his body. Nonetheless, under specific circumstances relatives decide not to take revenge, performing what I refer to as 'anti-revenge'. Ethnographic analysis of relations among victims, aggressors, and avengers reveals how alternation between relational excess and fissures makes individuation possible. The processes responsible for the composite character of personhood lead to a relational excess that needs to be restrained. The relation between revenge and anti-revenge is a key aspect of a Qom understanding of personhood, in which individuation needs to be achieved to avoid indifferentiation.